A Diachronic Archaeometallurgy Study of Metal Fishhooks in Huanchaco: Alloys and Manufacturing Techniques - Vetter-Parodi, L.; Prieto, G.; Ruíz, J.; Aldama-Reyna, C.; Ocharán, G.; Agreda-Delgado, J. (John Wiley and Sons, 2025)
ABSTRACT Archaeological excavations at three sites in Huanchaco, Moche Valley, North Coast of Peru, have yielded metal fishhooks in domestic and funerary context occupations from 150/50 bc to ad 1530. The marine‐oriented nature of the Huanchaco occupations points to the necessity of using metal fishhooks in their daily subsistence activities. However, metal fishhooks seem to have been of more exclusive usage rather than of common availability. This article focuses on the results obtained through optic microscopy, X‐ray fluorescence and scanning electron microscopy with disperse spectrometry energy and digital radiographic imagery done on the metal of these artefacts. We conclude that copper was the preferred metal during all periods. However, there are slight differences in the alloys employed within and between societies and time periods, while the manufacturing technique seems to have been the same (plastic deformation and annealing) with a few variances over time.
Keywords: Context (archaeology); Metal; Copper; Subsistence agriculture; Deformation (meteorology); Scanning electron microscope; https://purl.org/pe-repo/ocde/ford#1.03.00